Sovereignty In ASEAN and The Problem of Maritime Cooperation in the South China Sea - JN, Mak (2016)
ASEAN is notable for the ‘long peace’ in the region that has existed since the 1980s. Most analysts have attributed this success to the norms enshrined in the 1976 ASEAN Treaty of Amity and Cooperation (TAC), and which the members have accepted as an intrinsic part of their intra-ASEAN and international relations. However, this paper argues that the ‘long peace’ applied only to interactions and developments on land. In contrast, a ‘conflict-threat’ process, including militarization of disputes, has marked ASEAN relations in contested maritime zones, especially in the South China Sea and the Celebes Sea. This is in complete variance with the norms of the ‘ASEAN way, which endorses non-use of threat or force in addressing conflicts. This is because two different realms exist within ASEAN – the terrestrial and the maritime – where different norms apply. This paper argues that a ‘state of nature’ exists in contested maritime zones, with ASEAN members engaged in boundary making. This explains why cooperation at sea has been highly problematic, in contrast to the terrestrial realm where territorial boundaries/sovereignties have been clearly established. Fundamentally, the ‘ASEAN way’ still does not apply to the maritime realm, and cooperation at sea will thus be difficult to achieve. Successful joint development and cooperation in the Gulf of Thailand in fact confirms the argument.